1996
DOI: 10.1103/physrevb.54.1187
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous behavior and magnetic field and pressure effects onLa2/3Ca1

Abstract: The effects of magnetic field and pressure on the unusual spontaneous behavior of La 2/3 Ca 1/3 MnO 3 have been thoroughly investigated. Resistivity and volume thermal expansion, both under magnetic field and pressure, ac susceptibility under pressure, magnetostriction, magnetoresistance, and neutron diffraction measurements, have allowed us to determine the relevant underlying mechanisms in this system. Above T c the neutron measurements reveal short-range ferromagnetic correlations and the anomalous volume t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(116 citation statements)
references
References 38 publications
10
104
1
1
Order By: Relevance
“…To explain, for instance, the large magnetoresistance effect, strong electron-phonon interaction arising from the Jahn-Teller splitting of Mn d levels was added to these early theories to support the drastic change of electronic bandwidth observed at the transition [7]. Further studies concluded that the local distortion revealed by an anomalous thermal expansion between the Curie-Weiss transition temperature T C and a higher temperature T * pointed towards the presence of ferromagnetic clusters or polaronic interactions being responsible for the electrical conduction [8][9][10]. The presence of clusters in the paramagnetic (PM) region was associated with signature magnetic behavior observed in Griffiths phases [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To explain, for instance, the large magnetoresistance effect, strong electron-phonon interaction arising from the Jahn-Teller splitting of Mn d levels was added to these early theories to support the drastic change of electronic bandwidth observed at the transition [7]. Further studies concluded that the local distortion revealed by an anomalous thermal expansion between the Curie-Weiss transition temperature T C and a higher temperature T * pointed towards the presence of ferromagnetic clusters or polaronic interactions being responsible for the electrical conduction [8][9][10]. The presence of clusters in the paramagnetic (PM) region was associated with signature magnetic behavior observed in Griffiths phases [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The strain can also be caused by the lattice-substrate mismatch 1,19 . This kind of epitaxial strain is different from the strain induced by hydrostatic 20 or chemical pressure 17,18 , since an in-plane strain generally accompanies an out-of-plane strain with different sign, which can cause new electronic behavior did not found in bulk materials of the same chemical composition 1 . The interplay between substrate and film allows the modification of properties and can even enhance the magnetoresistive effect 5,21 .…”
Section: Introductionmentioning
confidence: 99%
“…This pressure parameter is small in comparison to the same parameters obtained usually on manganites which can reach value of about dT C /dp = +23.4 K/GPa as it was determined for La 0.67 Ca 0.33 Co 0.03 Mn 0.97 O 3 ceramic prepared by the same technique [16]. The increase of T C is usually attributed to the pressure induced increase of the electronic band width W due to increase of the bonding angle and reduction of the bond length of Mn-OMn [17,18]. Magnetization µ measured in both ZFC and FC regimes increases with applied pressure.…”
Section: Resultsmentioning
confidence: 99%